Temporary beam-to-column connection for precast concrete frame assembly. (15th September 2018) - Araújo, Daniel de Lima; Prado, Lisiane Pereira; Silva, Erlucivânia Bueno da; El Debs, Mounir Khalil
Graphical abstract: Highlights: A temporary beam-to-column connection is proposed. A fast-temporary beam-to-column connection with adequate torsion strength is proposed. The beam-to-column connection is analysed by tests and computational modelling. The steel strap of the Cazaly Hanger device is replaced by steel rebars. It is shown that a U profile steel corbel can achieve a partial flexure yielding strength. Abstract: Several types of connections have been developed for precast structures, many of them with a focus on the beam-to-column connection. An important aspect of the design of these connections is to ensure the safety of the construction building during the assembly of the precast elements, which necessarily takes into account the safety of the temporary beam-to-column connection. Therefore, this paper presents a study of a beam-to-column connection for the assembly stage compound by a U profile steel corbel embedded in the column that support a cantilevered steel tube in the beam extremity, so-called Cazaly-Hanger device. The cantilevered steel tube fits in the U profile steel corbel that restricts the beam tipping. The results of the tests indicate that the proposed connection shows potential to be applied in the assembly phase of precast structures, having adequate torsion strength, against beam tipping, up to a loading equivalent of 60% of the theoretical strength of the steel corbel. The U profile steel corbel showed partial flexural yielding of the cross-section and ultimate load up to 38% higher than the value predicted by the analytical model. In addition, the results show that the steel strap used in the Cazaly Hanger device can be replaced by steel rebars welded to the profile without compromising its strength. The connection tested was computationally modelled using a finite element computational package, and a good agreement with results of the test was showed. Then, two proposals for modifying the connection by used wedding were analysed through the computational modelling. Results show that the connection strength can be increased by up to 17% due to better continuity of the corbel and cantilevered tube in the assembly stage.